Development of a short form of the Hong Kong Chinese orebro musculoskeletal pain screening questionnaire - Raymond C. C. Tsang; Edwin W. C. Lee; Jamie S. Y. Lau; Susane S. F. Kwong; Eric M. L. So; Thomas F. Y. Wong; Rainbow K. Y. Law (Hong Kong Physiotherapy Journal, 2019)
Background: The Orebro Musculoskeletal Pain Screening Questionnaire (OMPSQ) is a valid screening tool to identify those musculoskeletal patients at risk of developing chronicity and disability. A Hong Kong Chinese version of the OMPSQ (COMPSQ-HK) was developed with satisfactory construct validity and predictive validity. Objective: The aim of this study was to develop a 10-item short form of the COMPSQ-HK (COMPSQ-HK10) and examine its measurement properties. Methods: The 10 items were identified from the suggestion by the original author of OMPSQ. The data of the 10 items were extracted from the main study to develop the COMPSQ-HK conducted from 2010 to 2013. The internal consistency using Cronbach’s alpha, test–retest reliability examining intraclass correlation coefficient (ICC1,1), minimum detectable change and 95% limits of agreement, construct validity by correlating COMPSQ-HK10 with pain, disability score, kinesiophobia score and Medical Outcomes Study Short Form 12, and predictive validity investigating receiver operating characteristic (ROC) curve analyses with sick leave >60 days and return-to-work status at one year were calculated. Results: A total of 305 back patients and 160 neck patients were recruited with about 30% of patients lost to follow-up at one year. Both the internal consistency (Cronbach’s alpha as 0.732 to 0.757) and test–retest reliabilities (ICC1,1 as 0.868 for both back and neck patients) were satisfactory. The correlations between COMPSQ-HK10 and COMPSQ-HK for back and neck patients were excellent (Pearson r as 0.919 and 0.896, respectively, p<0.001). The areas under the ROC curves for back and neck patients were similar for COMPSQ-HK10 and COMPSQ-HK, ranging from 0.603 to 0.712. A cut-off score of 54 of COMPSQ-HK10 was recommended in predicting “sick leave of more than 60 days at one year” and “return to work for at least four consecutive weeks at one year”. Conclusion: The COMPSQ-HK10 has comparable measurement properties with the COMPSQ-HK. It is recommended to use the COMPSQ-HK10 for routine screening to identify patients of back and neck pain at risk of developing chronic pain and disability.